Study of coal gas wettability for CO2 storage and CH4 recovery. Issue 3 (14th March 2014) - Saghafi, A.; Javanmard, H.; Pinetown, K.
Abstract To quantify and rank gas wettability of coal as a key parameter affecting the extent of CO2 sequestration in coal and CH4 recovery from coal, we developed a contact angle measuring system based on a captive gas bubble technique. We used this system to study the gas wetting properties of an Australian coal from the Sydney Basin. Gas bubbles were generated and captivated beneath a coal sample within a distilled water‐filled (pH 5.7) pressurised cell. Because of the use of distilled water, and the continuous dissolution and shrinkage of the gas bubble in water during measurement, the contact angles measured correspond to a 'transient receding' contact angle. To take into account the mixed‐gas nature (CO2, CH4, and to a lesser extent N2) of coal seam gas in the basin, we evaluated the relative wettability of coal by CH4, CO2 and N2 gases in the presence of water. Measurements were taken at various pressures of up to 15 MPa for CH4 and N2, and up to 6 MPa for CO2 at a constant temperature of 22°C. Overall, our results show that CO2 wets coal more extensively than CH4, which in turn wets coal slightly more than N2. Moreover, the contact angle reduces as the pressure increases, and becomes < 90° at various pressures depending on the gas type. In other words, all three gases wet coal better than water under sufficiently high pressure.